2018
DOI: 10.14303/irjm.2018.017
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Properties, Phytochemical Composition, and Phenotypic Resistance Pattern of Selected Enteropathogenic Microorganism on Ageratum conyzoides (Goat Weed) Leaf Extract

Abstract: The aim of this study is to determine the phytochemical composition, antimicrobial properties and phenotypic resistance pattern of selected enteropathogenic microorganism on Ageratum conyzoides leaf extract. Enteropathogenic isolates were collected from Adekunle Ajasin University Health Centre, Akungba Akoko, Ondo State and were identified using Microbact™ 24E Identification kit. Antibiotic sensitivity testing was carried out against the enteropathogenic organism using Kirby-Bauer disc diffusion method, imipen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…indicates that secondary metabolites such as alkaloids, flavonoids, saponins, tannins, quinones, steroids, and triterpenoids are present in Bandotan leaves. These results are consistent with the results of the phytochemical screening of Osuntokun et al[4], who stated that A. Conyzoides leaves contained alkaloids, flavonoids, tannins, saponins, steroids, phenols, and anthraquinones.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…indicates that secondary metabolites such as alkaloids, flavonoids, saponins, tannins, quinones, steroids, and triterpenoids are present in Bandotan leaves. These results are consistent with the results of the phytochemical screening of Osuntokun et al[4], who stated that A. Conyzoides leaves contained alkaloids, flavonoids, tannins, saponins, steroids, phenols, and anthraquinones.…”
supporting
confidence: 92%
“…Based on a review by Janarthanan et al [3], Bandotan leaves are traditionally used as a wound healer, antiinflammatory, analgesic, antipyretic, antispasmodic, gastroprotective, antimicrobial, antidiabetic, anticancer, antiulcer, antioxidant, hematopoietic, larvicidal, mosquito repellent, insecticide, and anthelmintic. Phytochemical analysis of Bandotan leaf extract showed the presence of alkaloids, flavonoids, tannins, saponins, reducing sugars, steroids, phenols, cardiac glycosides, and anthraquinones [4]. Yusnawan and Inayati [5] reported that the flavonoids in leaf and flower extracts were four times higher than in stem and root extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that phyto-additives containing rich bioactive compounds can stimulate feed intake, facilitate nutrient digestion and absorption in the gut through secretion of endogenous digestive enzymes and enlargement of villi diameters, thereby improving the broiler chickens' BWG (Mohiti-Asli and Ghanaatparast-Rashti, 2017, Oloruntola et al, 2018. Also, GLM and WLM are known to possess antibacterial, antifungal and antiprotozoal properties (Gutierrez et al, 2015;Osuntokun et al, 2018) which can suppress harmful microbes and promote intestinal health and stimulate growth in broiler chicken than the birds fed the control diet and antibiotic supplemented diet as seen in this current study.…”
Section: Resultsmentioning
confidence: 99%
“…Ekstrak etanol herba alfalfa mengandung fl avonoid dengan kadar total 8,13 %, alkaloid dengan kadar 48,86 ppm dan kumarin dengan kadar 229,83 ppm (5) . Flavonoid dari golongan fl avonol, fl avon dan isofl avon potensial sebagai antiinfl amasi yang mampu menghambat asam arakhidonat yang akan memproduksi prostaglandin (6) serta antibakteri dengan merusak dinding sel, menonaktifkan kerja enzim, dan merusak membran sel (7) . Ekstrak etanol herba alfalfa (Medicago sativa L.) mengandung flavonoid dan memiliki aktivitas antibakteri terhadap Staphylococcus aureus, Streptococcus pyogenes, Proteus mirabilis, Bacillus cereus, Escherichia coli, Pseudomonas aeruginosa, Salmonella thypi dan Klebsiella pneumonia dengan metode difusi agar sumuran.…”
Section: Pendahuluanunclassified